Features of the audit of allowances for doubtful debts ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses the relevance of choosing an approach to planning and conducting audit procedures for testing the allowance for doubtful debts. The main stages of the audit of accounts receivable and the analysis of the risks of its non-return are considered. The accounting of the reserve for doubtful debts as an estimated value is analyzed. The reflection of receivables in financial statements, considering the reserve for doubtful debts, and the risks of its misstatement are considered. The normative-legal acts regulating the accounting of receivables and the formation of the corresponding reserve are analyzed
Keywords: accounts receivable; audit; audit procedures; doubtful accounts receivable; allowance for doubtful debts